QoS Support in TLMM: Three Level Mobility Model for IP-Based Networks - Chakraborty, Mohuya; Misra, Iti Saha; Saha, Debasish; Mukherjee, Amitava (Distributed Computing - IWDC 2004, 2004)
TLMM, a three level mobility model for IP-based mobility management has been recently proposed as an architecture for managing global mobility in an IP-based network. This paper evaluates the performance of TLMM’s Quality of Service (QoS) framework using a combination of DiffServ and IntServ architectures with the concept of Bandwidth Broker for admission control and resource reservation for different service classes. The most important contribution in this paper is a dynamic handoff policy using the concept of Boundary Location Area, for performing location updates for inter-domain roaming of mobile nodes, which helps in maintaining proper QoS. The performance evaluation of the proposed protocol is provided by simulation results using Network Simulator (ns-2).